Strategic integration of generative ai in design artifact ideation: proposal of a structured framework - Larrazábal, Rodrigo R.; Alexandre, Gustavo H. (Companion Proceedings of the Brazilian Symposium on Information Systems (SBSI); 2025: Companion Proceedings of the 21st Brazilian Symposium on Information Systems, 2025)
This paper proposes a structured framework for strategically integrating Generative Artificial Intelligence (GAI) into the design ideation process, aiming at optimizing artifact creation while preserving designers' creative autonomy. Grounded in the Design Science Research (DSR) methodology, the framework was validated through a controlled quasi-experiment. Quantitative results showed a significant 40% reduction in ideation time and a substantial 60% increase in creative variability. Qualitative analysis confirmed participants' positive acceptance, emphasizing the framework’s flexibility and ease of customization. Nevertheless, challenges emerged regarding the initial training required for users, as well as concerns about originality and ethical implications of AI-generated content.